Modul matematika pada materi relasi dan fungsi untuk siswa MTs kelas VIII berbasis kontekstual dan terintegrasi nilai-nilai keislaman - Atsnan, Muh. Fajaruddin (Math Didactic: Jurnal Pendidikan Matematika, 2023)
This research aims to describe the development of mathematics teaching materials in the form of modules based on a contextual approach integrated with Islamic values for relationship and function material, and to obtain information on the quality of the modules created. This module covers Islamic values, such as prayer, almsgiving, the good qualities of the Prophet, as well as good habits dictated by religion. This research and development model follows the ADDIE reference. The research results explain that (1) the validity of the module is in the "Good" criteria according to the validation results from 2 expert lecturers (material experts and media experts), (2) the practicality of the module gets the "Good" criteria, with 50 out of 57 students or 87.72 % answered that they strongly agreed that the module was easy to understand in terms of material and its content had an Islamic content, (3) the effectiveness of the module based on the learning outcomes test showed that 52 out of 57 students achieved the minimum ability criteria (KKM) set by the school, namely 68, with a completion percentage of 91.23% and the average value is 81.04.